Analysis of online learning process during the Covid-19 Pandemic in primary school teachers - Pamungkas, Dyan Eka; Sukarman, Sukarman; Purnomo, Bambang (International Journal for Educational and Vocational Studies, 2021)
This study aims to described the analysis of difficulties and efforts of teachers in online learning at SDN Airlangga III/200 Surabaya. This research uses qualitative descriptive method research, information collection method using online observation, interview, and documentation. The data analysis method used in this study is data reduction, data presentation and conclusion drawing. Researchers act as data collection instruments. The results showed that the difficulties that teachers felt in online learning during the Covid-19 Pandemic were insufficient facilities, material completion and assessment. The efforts that teachers try to overcome the difficulties felt is by sharing supporting internet access, various assignments, as well as cooperation with the school, teachers and parents of students. The impact obtained after efforts to improve online learning problems is a significant transformation in online learning during the Covid-19 Pandemic grade IV SDN Airlangga III/200 Surabaya.